2012
DOI: 10.1590/s1516-89132012000500007
|View full text |Cite
|
Sign up to set email alerts
|

Effect of probiotic administration on the immune response: a systematic review of experimental models in rats

Abstract: The probiotic influence on the immune system, especially under pathogenic challenge conditions, still remains controversial. To address this, a systematic review of current studies concerning the efficacy of probiotics on the immune response of rats subjected to experimental challenges was conducted. The survey was conducted using PubMed, ISI Web of Science and Scielo databases. Only studies which tested probiotics in vivo in rats were included. The experimental design, methodological quality, and results of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 62 publications
0
9
0
2
Order By: Relevance
“…Probiotic bacteria reduce lactose intolerance symptoms, such as diarrhea and flatulence, which appear in lactose intolerant patients who consume milk. Probiotic bacteria also increase the immune response toward pathogens by inhibiting pathogen colonization in the GI tract [ 59 ] and promote the mucosal immune system by activating plasma cells, inducing secretion of immunoglobulin A (IgA) and migration of T cells [ 71 ].…”
Section: Lactic Acid Bacteria As the Dna Vaccine Carriermentioning
confidence: 99%
“…Probiotic bacteria reduce lactose intolerance symptoms, such as diarrhea and flatulence, which appear in lactose intolerant patients who consume milk. Probiotic bacteria also increase the immune response toward pathogens by inhibiting pathogen colonization in the GI tract [ 59 ] and promote the mucosal immune system by activating plasma cells, inducing secretion of immunoglobulin A (IgA) and migration of T cells [ 71 ].…”
Section: Lactic Acid Bacteria As the Dna Vaccine Carriermentioning
confidence: 99%
“…However, it has been reported that probiotics play a major role in the control of intestinal and non-gut parasite infections [16]. Adequate administration of probiotics in patients found to stimulate the immune response against pathogens [18]. Modulated the immune system by stimulating the host immune response to a variety of pathogens [19].…”
Section: Introductionmentioning
confidence: 99%
“…As formas patogênicas de salmonelas não compõem esta microbiota que mantém o estado de higidez das aves domésticas (Salanitro et al, 1974). Com base nas características microbiológicas do lúmen intestinal, as culturas de probióticos são elaboradas com bactérias não patogênicas normalmente derivadas da microbiota normal que contribuem para exclusão de bactérias patogênicas no epitélio intestinal e para melhora significativa da resposta imune dos animais (Silva et al, 2012). O repovoamento do trato gastrintestinal com bactérias benéficas após eventos agressores da microbiota como enterites de origem bacteriana ou viral pode ser evitado pela inoculação contínua de cultivos probióticos que têm a capacidade de reduzir a ação bacteriana indesejável.…”
Section: Mecanismo De Açãounclassified